Conformal solution model for the thermodynamic properties of antimonyindium liquid alloys - Chakrabarti, SK; Jha, IS; Jha, BK; Singh, BP (Scientific World, 2011)
In the present work we have considered the antimony-indium liquid alloy which shows anomaly as regards its heat of mixing and the concentration fluctuations in the long-wavelength limit. On the other hand, the free energy of mixing and the entropy of mixing are found to be symmetric about the equi-atomic composition. Such alloying behaviour has been tried to explain on the basis of conformal solution model. This is a statistical mechanical model based on the formation of complex within the liquid alloy. In this model besides the interaction between unlike atoms, that between each constituent element and the complex too is taken into account. In course of theoretical treatment the activity of antimony is also computed for different concentrations. Our results indicate that Sb-In alloys are thermodynamically most stable around the equi-atomic composition. Key words: Binary liquid alloy; Conformal solution model; Free energy of mixing; Activity; Heat of mixing; Entropy of mixing; Concentration fluctuations in the long-wavelength limit. DOI: http://dx.doi.org/10.3126/sw.v9i9.5510 SW 2011; 9(9): 13-15